Repetitive blast mild traumatic brain injury increases ethanol sensitivity in male mice and risky drinking behavior in male combat veterans. (9th April 2021) - Schindler, Abigail G.; Baskin, Britahny; Juarez, Barbara; Janet Lee, Suhjung; Hendrickson, Rebecca; Pagulayan, Kathleen; Zweifel, Larry S.; Raskind, Murray A.; Phillips, Paul E.M.; Peskind, Elaine R.; Cook, David G.
Abstract: Background: Mild traumatic brain injury (mTBI) is common in civilians and highly prevalent among military service members. mTBI can increase health risk behaviors (e.g., sensation seeking, impulsivity) and addiction risk (e.g., for alcohol use disorder (AUD)), but how mTBI and substance use might interact to promote addiction risk remains poorly understood. Likewise, potential differences in single vs. repetitive mTBI in relation to alcohol use/abuse have not been previously examined. Methods: Here, we examined how a history of single (1×) or repetitive (3×) blast exposure (blast‐mTBI) affects ethanol (EtOH)‐induced behavioral and physiological outcomes using an established mouse model of blast‐mTBI. To investigate potential translational relevance, we also examined self‐report responses to the Alcohol Use Disorders Identification Test‐Consumption questions (AUDIT‐C), a widely used measure to identify potential hazardous drinking and AUD, and used a novel unsupervised machine learning approach to investigate whether a history of blast‐mTBI affected drinking behaviors in Iraq/Afghanistan Veterans. Results: Both single and repetitive blast‐mTBI in mice increased the sedative properties of EtOH (with no change in tolerance or metabolism), but only repetitive blast potentiated EtOH‐induced locomotor stimulation and shifted EtOH intake patterns. Specifically, mice exposed to repetitive blasts showed increased consumption "front‐loading" (e.g., a higher rate of consumption during an initial 2‐h acute phase of a 24‐h alcohol access period and decreased total daily intake) during an intermittent 2‐bottle choice condition. Examination of AUDIT‐C scores in Iraq/Afghanistan Veterans revealed an optimal 3‐cluster solution: "low" (low intake and low frequency), "frequent" (low intake and high frequency), and "risky" (high intake and high frequency), where Veterans with a history of blast‐mTBI displayed a shift in cluster assignment from "frequent" to "risky, " as compared to Veterans who were deployed to Iraq/Afghanistan but had no lifetime history of TBI. Conclusions: Together, these results offer new insight into how blast‐mTBI may give increase AUD risk and highlight the increased potential for adverse health risk behaviors following repetitive blast‐mTBI.